Cathodic voltammetric detection of diltiazem at a bismuth film electrode: application to human urine and pharmaceuticals - Catarino, Rita I. L. (2014)
In this work it was developed a novel application of bismuth film electrodes (BiFEs) for the determination of the antihypertensive and coronary vasodilator diltiazem by square wave cathodic voltammetry. The bismuth film was deposited ex situ on a glassy carbon electrode for 90 s at -1.4 V vs. Ag/AgCl, from an acetate buffer (pH 4.5; 0.10 mol L-1) containing 5 or 30 mg L -1 Bi. Diltiazem analytical signal was obtained in phosphate buffer (pH 7.4; 0.25 mol L-1) where reduction takes place at -1.5 V vs. Ag/AgCl. The proposed methodology was applied to the quantification of diltiazem in pharmaceutical samples (dynamic linear range comprised between 90 and 900 μg L-1) and in human urine (dynamic linear range comprised between 45 and 270 μg L-1, and detection limit of 12 μg L -1).